Morphological Characterization of Coffee Plants (Coffea Sp.) in Leihitu District, Central Maluku Regency - Ardiansyah, Andi; Mahulette, Asri Subkhan; Marasabessy, Dessy Ariyani (Fakultas Pertanian Universitas Darussalam Ambon, 2024)
Coffee plants are one of the plantation commodities that have been cultivated for generations by farmers in Leihitu District, Central Maluku Regency. So far, there has not been much information about various studies related to the morphological diversity of these commodities. The research aims to analyze the morphological and descriptor characteristics of coffee plants cultivated in Leihitu District, Central Maluku Regency. The research was carried out in three coffee plant distribution locations in Leihitu District, Central Maluku Regency, namely Seith, Hitulama, and Hitumessing Villages in December 2023 - February 2024. The results of the morphological analysis of coffee plants which were characterized using Hierarchical Cluster Analysis (HCA) based on 69 morphological characters showed two groups with a dissimilarity coefficient of 20%, where the first group consisted of 29 accessions that were clustered with 84% similarity, while the second group only consisted of one accession with dissimilarity coefficient of 20% to the first group. The results of Principle Component Analysis (PCA) on coffee plants showed characteristic characters in the form of leaf length, leaf area, leaf width, stipule diameter, plant height, green bean weight and mature bean length. The characterization results provide information that the type of coffee cultivated by farmers in Leihitu District, Central Maluku Regency is Robusta coffee.